Effects of Campylobacter fetus on bull sperm quality - Cagnioli, Claudia Inés; Chiapparrone, María Laura; Rodríguez, Marcelo Gastón; Aller Atucha, Juan Florencio; Catena María del Carmen; Cacciato, Claudio Santiago (Elsevier, 2020)
Campylobacter fetus is a gram-negative, motile, spiral or S-shaped bacterium, which induces campylobacteriosis. This disease causes decrease productivity of cattle. Although considerable research has been done on the role of C. fetus on female fertility, little is known about the effect on bulls. The aim of this work was to evaluate the effect of C. fetus subsp. fetus (Cff) and C. fetus subsp. venerealis (Cfv) on bull sperm quality. Samples of frozen semen (n = 29 straws) were each distributed into three groups: two of them incubated with the microorganism (Cff, Cfv) and a control group. The proportions of live spermatozoa, with functional membrane and true acrosomal reaction in control group were significantly (P < 0.01) greater than those observed in Cff and Cfv groups. However, no significant differences (P > 0.05) were found in sperm chromatin structure among treatments. In adhesion assay, proportions of spermatozoa with adhered Campylobacter were similar for both subspecies. Results confirm that Cff and Cfv have the same ability to bind in an irreversible way to bull spermatozoa and to affect sperm quality. It is proposed that adherence could be considered as the main cause of sperm alterations, and also an important step of pathogenesis and venereal transmission.